Communication matters: Sensitivity in fairness evaluations across wealth inequality expressions and levels - Annalena Oppel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper seeks to understand whether the way in which inequality is communicated through measurements influences individuals' fairness perceptions regarding wealth inequality. It begins from the premise that prominent measures of inequality, such as the Gini coefficient, fall short of providing an intuitive understanding of inequality for most people. Following approaches in the behavioural economics domain, the paper explores the effects of four different presentations of inequality in a survey experiment. In this way it aims to see whether individuals' fairness evaluations change across different levels of inequality. To do so, it introduces three different inequality scenarios, respectively corresponding to Gini coefficients of 32.8, 46.8, and 60.3. The scenarios are presented using different expressions: large-stake and small-stake units for absolute expressions, and percentages and multiples for relative expressions. The results point to a notable difference in fairness evaluations based on whether respondents are presented with absolute versus relative expressions of inequality: absolute expressions lead to a larger decline in fairness evaluations for higher levels of inequality. More broadly, the paper's contribution highlights the importance of 'intuitive' measures of political matters such as wealth inequality. It further indicates that this may be particularly vital in highly unequal countries such as South Africa. This concerns public and policy discourses alike. The paper suggests avenues for further exploration to bring more nuance and context to the patterns observed.
Keywords: D31; D83; D90; I0; 330; fairness perceptions; inequality; survey experiment; wealth; measurement